John Woo's The killer - Hall, Kenneth E., 1954- (New Hong Kong cinema., 2009)
Has the creative period of the New Hong Kong Cinema now come to an end? However we answer this question, there is a need to evaluate the achievements of Hong Kong cinema. This series distinguishes itself from the other books on the subject by focusing in-depth on individual Hong Kong films, which together make the New Hong Kong cinema.